Switching from Antipsychotic Polypharmacy to Monotherapy in Hebephrenic Schizophrenia: A Case Study - Silaban, Rusdiana; Nur Azizah; Hafid Algristian (Yayasan Sinergi Kawula Muda, 2026)
Schizophrenia is a chronic psychiatric disorder that imposes a substantial burden on patients and caregivers. Antipsychotic polypharmacy remains a common clinical practice to manage persistent positive and negative symptoms, although growing evidence indicates it does not significantly improve treatment outcomes and may instead increase adverse effects, treatment costs, and non-adherence. This case study aimed to describe the clinical benefits and rational considerations of switching from antipsychotic polypharmacy to monotherapy in a patient with hebephrenic schizophrenia. A 37-year-old woman with a 20-year history of hebephrenic schizophrenia was observed. She had previously received a combination of chlorpromazine and trifluoperazine with trihexyphenidyl for extrapyramidal symptom prevention. Clinical evaluations were performed to assess therapeutic effects, side effects, and medication adherence before and after the switch to chlorpromazine monotherapy. During the polypharmacy phase, the patient experienced several side effects, including insomnia, restlessness, irritability, and mild extrapyramidal symptoms. After transitioning to monotherapy with an adjusted chlorpromazine dose, she showed notable improvement in psychotic symptoms, sleep quality, and social functioning without severe adverse reactions. Medication adherence increased as the patient reported greater comfort and tolerance with a single-drug regimen. This case suggests that switching from antipsychotic polypharmacy to monotherapy can reduce side effects, improve adherence, and maintain clinical stability. Rational and individualized use of antipsychotics should be prioritized to achieve better long-term outcomes and quality of life in schizophrenia management.